( Studi pada KPRI Keluarga Besar Guru (KBG) Kota Kecamatan Tulungagung) - Navila, Neneng; Eko Sujianto, Agus (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
This is study aims to analyze the effect of loan capital and business volume on the remaining results of operations (SHU) with total assets as the intervening variable at KPRI Family Teacher (KBG KOTA) Tulungagung District. This research approach uses quantitative methods. Quantitative research is systematic scientific research on parts and phenomena and their relationships. This type of research uses associative research, namely research conducted to determine the relationship between two or more variables. This study uses data on loan capital, business volume, remaining operating results (SHU), and total assets in the 2012-2021 period, where the data was obtained from KPRI using the documentation method and the interview method. In this interview technique there is a process of interaction, discussion and presentation. The analysis technique used is moderated regression analysis (MRA) and begins with several prerequisite tests, heteroscedasticity test, multicollinearity test and others. The results show that loan capital has no significant effect on the remaining operating results (SHU) of cooperatives. Business volume has a significant effect on the Cooperative's Remaining Results of Operations (SHU). Then the total assets are able to strengthen the influence of loan capital and business volume on the Remaining Results of Operations (SHU) of the KBG KOTA cooperative, Tulungagung District